Teologi Rasional Ijtihad Dan Dogmatis Taqlidi Penalaran Filsafat Kalam - Teuku Safir Iskandar Wijaya (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
The ideas of rational theology and dogmatic theology are closely related to the concept of taqlid and ijtihad in the development of Islamic theological thought. Even, both theologies have caused serious debates among Islamic thinkers and mutakallim from time to time. In this relation, two different ideas arise; some say the door of ijtihad is closed for everything; in addition, there is also a view that the door of ijtihad only closed in relation to theological belief, and still open for muamalah problem, and law related to humanity problem. The question that arises in this connection is "why the previous theological problem as a result of political disputes becomes a dogma of justification and is seen getting a serious attention even to threaten the dispute between people and even between schools and schools. Furthermore, the ruler also uses certain schools to reinforce their power and position in politics. Theology, therefore, serves as the object of creating to the dogma and not dialectical knowledge. In fact, the easy answer is the logic of theology or aqidah is the justification of belief and belief itself does not open the opportunity for dialogue for the different schools and streams of aqidah it embraces. Theology, however, as a science cannot be separated from the various interpretations and understandings derived from a dhanni and relative and can not be separated from the various doubts and prejudices that can not be separated from the various possibilities of understanding.